Development of student worksheet based on MEA model of ionic equilibrium and pH of buffer solution for Senior High School - Nelda Nelda; Betty Holiwarni; Lenny Anwar (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This research aims to develop a Student Activities Worksheet Based on the MEA Model on the ionic equilibrium and pH of buffer solution material for grade XI SMA/MA. Student Worksheet Based are designed according to the stage of the MEA learning model. The type of this research is research and development (R and D) about the development process of 4-D. The object of this research is student activities worksheets based on MEA. The data collection is the validation user response questionnaire. The validity of the content aspect obtained the result of data analysis, characteristics of MEA, language aspect, serve aspect, and visual aspect are 96.43%, 93.33%, 85.41%, 97.22%, 97.91% with valid category. Student activities worksheets validated by the validators tested to 25 students and three teachers. The test responses by 25 students and three chemistry teachers included very good criteria, with each score of 95% and 80.33%. Based on the result of data analysis, student activities worksheets based on MEA of ionic equilibrium and pH of a buffer solution produced are valid.